2014
DOI: 10.3390/molecules190811350
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin Induces S Phase Arrest and Apoptosis in Human Gallbladder Cancer Cells

Abstract: Gallbladder cancer is the most common malignant tumor of the biliary tract, and this condition has a rather dismal prognosis, with an extremely low five-year survival rate. To improve the outcome of unresectable and recurrent gallbladder cancer, it is necessary to develop new effective treatments and drugs. The purpose of the present study was to evaluate the effects of cordycepin on human gallbladder cells and uncover the molecular mechanisms responsible for these effects. The Cell Counting Kit-8 (CCK-8) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
4
30
1
Order By: Relevance
“…caspase-3 and Bax were associated with the apoptotic effect of cordycepin on H1975 cells. These results were consistent with the previous study where cordycepin induced apoptosis via downregulating the protein level of caspase-3 and Bcl-2 [25]. …”
Section: Cordycepin Induces Apoptosis and Regulates Apoptosis-relatedsupporting
confidence: 94%
See 1 more Smart Citation
“…caspase-3 and Bax were associated with the apoptotic effect of cordycepin on H1975 cells. These results were consistent with the previous study where cordycepin induced apoptosis via downregulating the protein level of caspase-3 and Bcl-2 [25]. …”
Section: Cordycepin Induces Apoptosis and Regulates Apoptosis-relatedsupporting
confidence: 94%
“…These indicated that down-regulation of caspase-3 and Bcl-2 and up-regulation of cleaved caspase-3 and Bax were associated with the apoptotic effect of cordycepin on H1975 cells. These results were consistent with the previous study where cordycepin induced apoptosis via down-regulating the protein level of caspase-3 and Bcl-2 [25]. caspase-3 and Bax were associated with the apoptotic effect of cordycepin on H1975 cells.…”
Section: Cordycepin Induces Apoptosis and Regulates Apoptosis-relatedsupporting
confidence: 93%
“…Our results showed that japonicone A treatment decreased the ΔΨm in all NSCLC cell lines, which indicates that japonicone A-induced apoptosis in NSCLC cells occurs via the mitochondria-related pathway. The disruption of the ΔΨm is recognized as an early stage of apoptosis, where the release of cytochrome c from mitochondria signals the initiation of apoptosis [15,16]. The mitochondria-dependent pathway is regulated by Bcl-2 family proteins, which are involved in apoptosis involving the pro-apoptotic proteins Bax [17,18].…”
Section: Japonicone a Induces Apoptosis In H441 And H520 Cellsmentioning
confidence: 99%
“…Data suggest that mitochondrial Ca 2++ handling accounts for spontaneous electrical activity, a step involved in gallbladder tone and motility (Balemba et al, 2008). Gallbladder mitochondria are also involved in other pathways such as drug-mediated effects on apoptosis during tumorigenesis in cells and mice (Bao et al, 2014;Li et al, 2015a;Liu et al, 2013;Shu et al, 2014;Wang et al, 2014;Weng et al, 2014) and treatment with oxysterols causing cytochrome c release in the dog (Seo et al, 2004). Both aspects are potentially linked to the aging process of the gallbladder with or without stone-formation ability.…”
Section: Gallstones Mitochondria and Agingmentioning
confidence: 99%